Evaluation of photolysis, photolysis/H2O2 and H2O2 as treatments for the reduction of Salmonella spp in water of pig farms - Valencia, Cynthia Lorena (2020)
The aim of this study was to evaluate three processes for the removal of organic matter and inactivation of Salmonella spp re inoculated in water from pig farms. Specific water samples were obtained to perform physical, chemical and microbiological characterization. Next, the operating conditions that favored the photolysis process were selected through a 2x2 factorial design. Finally, inactivation/removal kinetics were carried out, assessing UV254 nm photolysis, UV254 nm photolysis with hydrogen peroxide H2O2 at 15 ppm and hydrogen peroxide H2O2 at 15 ppm. The inactivation of Salmonella spp was favored by using an aeration of 1 L/min and with a concentration of Salmonella spp of 1x104 UFC/ml obtaining an inactivation of 97.3±1.9% after 10 minutes of treatment. On the other hand, for the inactivation kinetics it was established that the best treatments were photolysis and photolysis/H2O2, without significant differences. At 30 seconds of exposure, the inactivation of Salmonella was 99.9±2.4% in T1, with a removal of chemical oxygen demand (COD), NO3 and NO2 of 30±2, 27±3, 83±4, 41±1.0 and 99±5% for T1 and T2 respectively. The bacteria recovered in T2 and T3 and the treatments had no residual effect, determining that the final populations were 8 CFU/ml and 3x103 CFU/ml, respectively.